Anesthetic Management in Emergency Exploratory Laparotomy of Perforation Peritonitis in 92 Years Old patient: A Case Report - Rutu Shah; B J Shah; Anisha Choksi; Sonal Patel (Advances in Human Biology, 2015)
Background : Perforation peritonitis is a common surgical emergency. Geriatric patient presenting with perforation peritonitis is a challenge for an anaesthetist. Risk and outcome in such patients depend upon age, the patient′s physiological status, co-existing disease and whether the surgery is elective or emergency and type of procedure. Preoperative optimization, hemodynamic stability can reduce intraoperative and postoperative morbidity and mortality. Considering decreased physiological reserve of all body organs and systems intensive care in critical care setting is essential.